Development of an actual AB reactor using the harmonized automation system - Rabatan, Froilan E. (2000)
The problem that arises from automating control processes in industries has been a troubling one. Take an AB reactor system as an example. For one thing, integrating the subsystems of the production process (i.e. the heating, feeding, agitation etc.) requires different programmable controllers. These controllers in turn, needs a number of maintenance personnel to supervise these controllers. Scaled models of the system are also unavailable, which makes it even more difficult to study ways of improving plant operations. The use of the Harmonized Automation System (Harmonas) and a scaled model of an actual AB reactor would present a solution to the arising dilemma. Harmonas coordinates automation of the production process into a single harmonized controller. It provides a series of configurations that vary according to the demands of the application. Harmonas also employs Ethernet connections through its supervisory stations enabling human-to-machine-to-process interface. Since AB reactors employ a complete production process, modeling it and interfacing it with Harmonas would give the process industries a way of studying harmonized automation without compromising the actual system. We may then achieve integrated automation and control on a scaled model that leads to improved plant operation.